2017
DOI: 10.1093/jac/dkx273
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbapenem restriction on the antimicrobial susceptibility pattern of Pseudomonas aeruginosa isolates in the ICU

Abstract: These data suggest that restricting carbapenems, even for a short duration, may be an effective strategy for managing the problem of carbapenem resistance in P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 17 publications
5
38
0
1
Order By: Relevance
“…As a result, the comprehensive evaluation enables us to know that our intervention might promote optimal use of antimicrobials-that is, reduce unnecessary empirical carbapenem use and using narrow-spectrum antimicrobials such as rst-and third-generation cephalosporins-without a change in in-hospital mortality. Thus, we emphasize that not only a reduction in carbapenem consumption but also the positive impact of ASPs on optimizing the use of antimicrobials; the concepts supported by several previous reports [19,20].…”
Section: Discussionsupporting
confidence: 79%
“…As a result, the comprehensive evaluation enables us to know that our intervention might promote optimal use of antimicrobials-that is, reduce unnecessary empirical carbapenem use and using narrow-spectrum antimicrobials such as rst-and third-generation cephalosporins-without a change in in-hospital mortality. Thus, we emphasize that not only a reduction in carbapenem consumption but also the positive impact of ASPs on optimizing the use of antimicrobials; the concepts supported by several previous reports [19,20].…”
Section: Discussionsupporting
confidence: 79%
“…Restricting carbapenems even for a short duration has been suggested to effectively manage the problem of CRPA [ 20 ]. Our study indicated that carbapenem consumption is correlated with the rate of CRPA, similar to the conclusion of a previous study in China [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hypothesis 2 was supported ( Table 5). ln STAFF refers to ln PHY in model(5) and model (6), ln NUR in model (7) and model (8), ln PHA in model(9) and model (10) , ln MCB in model (11) and model (12).…”
Section: The Moderation Effect Test Of Medical Professionals Workloadmentioning
confidence: 99%